Peran Masyarakat Sipil dalam Mendukung Reformasi Administrasi Publik di Indonesia - Tripani Siahaan (CV. ITTC INDONESIA, 2026)
Public administration reform is an effort undertaken to improve government governance so that it is more effective, transparent, accountable, and responsive to the needs of the public. Civil society plays a vital role as a partner to the government and as a watchdog over the implementation of public policies during the reform process. The purpose of this study is to evaluate the role of civil society in supporting public administration reform and to identify the types of contributions they make toward fostering good governance. This study was conducted qualitatively using a literature review approach. Data were obtained from various sources, such as books, scientific journals, laws and regulations, and documents on public administration reform and civil society; data analysis was conducted through literature collection, reduction, presentation, and drawing of conclusions. The study shows that civil society can increase public participation, monitor government performance, enhance transparency and accountability, support policies, and empower communities through social and educational activities. Collaboration between the government and civil society can also strengthen democracy and support successful public administration reform. Therefore, to carry out these tasks effectively, the government must provide support through regulations, access to information, and the empowerment of civil society organizations.